2000
DOI: 10.1115/1.1366324
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Gas Turbines: A Newly Proposed Method of Exhaust Heat Recovery

Abstract: A new conceptual combination of Brayton and inverted Brayton cycles with a heat sink by intercooling, which is dubbed the mirror gas turbine, has been evaluated and proposed in this paper. Prior to such evaluations, a preliminary test on the inverted cycle without intercooling was made experimentally to confirm the actual operation. The conventional method of recuperation in gas turbines can be replaced by the mirror gas turbine with a low working temperature of about 450°C at heat exchanger. The combined cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 1 publication
0
10
0
2
Order By: Relevance
“…They found that a Brayton cycle with an IBC as a bottoming cycle had a thermal efficiency of over 60% for a turbine inlet temperature of 1500°C. Fuji et al [8] showed that the IBC could either replace a Rankine cycle as a bottoming cycle or could be used as an alternative to recuperation. Agnew et al [9] showed that overall efficiency could be improved with higher inverted cycle inlet pressures when used as a bottoming cycle.…”
Section: Figure 1: Inverted Brayton Cyclementioning
confidence: 99%
“…They found that a Brayton cycle with an IBC as a bottoming cycle had a thermal efficiency of over 60% for a turbine inlet temperature of 1500°C. Fuji et al [8] showed that the IBC could either replace a Rankine cycle as a bottoming cycle or could be used as an alternative to recuperation. Agnew et al [9] showed that overall efficiency could be improved with higher inverted cycle inlet pressures when used as a bottoming cycle.…”
Section: Figure 1: Inverted Brayton Cyclementioning
confidence: 99%
“…Así mismo, la búsqueda de alternativas para disminuir el trabajo de compresión conduce a aproximar un proceso de compresión a temperatura constante, utilizando dos o más compresores con enfriadores de tipo mecánico, evaporativo, etc. (Bassily, 2004;Fujii et al, 2001). Chen et al (2004), realizan el estudio de dos compresores con interenfriamiento variando la relación de presiones de compresión y por consiguiente la relación de presiones de enfriamiento, con el objetivo de suministrar el mínimo trabajo de compresión y mejorar la eficiencia térmica.…”
Section: Introductionunclassified
“…Furthermore, the performance optimization of an endoreversible closed Braysson cycle with heat resistance losses in the hot-side and cold-side heat exchangers was performed by using finite-time thermodynamics (FTT) [4,5] in 2002. Fujii et al [6] studied a bottom cycle constructed from an expander followed by an intercooled compression processes (mirror arrangement) in 2001. They limited the bottom cycle expansion pressure to 0.25 bar to avoid a rapid increase in gas flow axial velocity.…”
Section: Introductionmentioning
confidence: 99%